BMP6, a potential biomarker of inflammatory fibrosis and promising protective factor for dilated cardiomyopathy - Feng Jiang; Jiayang Tang; Xiaoqi Wei; Hai Pan; Xinyi Fan; Peng Zhang; Shuzhen Guo (Chinese Medicine)
Abstract Background Dilated cardiomyopathy (DCM) stands as one of the most prevalent and severe causes of heart failure. Inflammation plays a pivotal role throughout the progression of DCM to heart failure, while age acts as a natural predisposing factor for all cardiovascular diseases. These two factors often interact, contributing to cardiac fibrosis, which is both a common manifestation and a pathogenic driver of adverse remodeling in DCM-induced heart failure. Method Bulk RNA-seq, single-cell RNA-seq, Mendelian randomization analysis, animal model construction, and BMP6 knockdown were utilized to identify and validate potential specific markers and targets for intervention in DCM heart failure. Results We found that DCM hearts exhibit pronounced inflammatory cell infiltration and fibrosis. Both bulk RNA-seq and single-cell RNA-seq analyses revealed aberrant BMP6 expression specifically in fibroblasts. The ROC curve underscores the high specificity of BMP6 in relation to DCM, while Mendelian randomization analysis further confirms BMP6 as a protective factor against DCM. Notably, BMP6 knockdown led to a decrease in SMAD6 expression and a marked elevation in COL1A1 expression levels, indicating its antifibrotic role. Conclusion BMP6 emerges as a promising biomarker for DCM, and its functional role in exerting an antifibrotic effect underscores its potential as a therapeutic target.